Formation of methodological foundations for the analysis of national development in conditions of foreign economic discrimination - O. M. Pisareva (Модернизация, инновация, развитие, 2024)
Purpose: is to form a conceptual approach to the analysis of the macroeconomic effects of external sanctions based on increasing the information content of the use of technical indicators in assessing the stability and vulnerability of the national economy to the effects of discriminatory restrictions in foreign economic activity. Methods: the study is based on the processing and analysis of data obtained as a result of content analysis of a significant number of scientific, scientific-practical, and expert sources of information.Methods of scientific generalization and classification, economic, expert and statistical analysis were used.Results: the analysis of the impact of sanctions restrictions on the key indicators of the characteristics of sustainable and innovative development of the discriminated national economy is carried out. An approach to assessing the impact of sanctions is presented based on a conjugate analysis of the dynamics of target groupings of indicators. An example of calculations, visualization and interpretation of the results of assessing sanctions resistance and export-import dependence of the national economy based on a set of technical indicators for significant areas of socio-economic development of the discriminated country is illustrated. The scope of application of the proposed approach in the formation of the development strategy and program (in terms of the implementation of the process of import substitution, ensuring technological independence and structural adaptation of the economy) is justified, taking into account the risks of sanctions restrictions.Conclusions and Relevance: the proposed approach to the analysis of sanctions restrictions based on the combined use of technical criteria for the dynamics of grouped indicators provides an increase in the reliability of estimates of their negative impact. However, aggregated estimates do not allow us to justify selective and targeted measures aimed at adapting the institutional and organizational conditions of the activities of specific economic agents in key areas of the national economy. A possible direction for further research may be the development of methodological and analytical tools for assessing the sanctions stability of economic sectors to substantiate the priorities of ensuring their technological independence.